Mortality in older adults as an outcome of the association of depressive symptoms and 25(OH)D deficiency: an integrative review (Research, Society and Development, 2023)
Depression is a disease that causes great disability and has a high prevalence among the older adults. Also of expressive distribution is the deficiency of vitamin D, which favors the development of depressive symptoms. Both depression and low vitamin D levels are predictors of higher mortality. This integrative review aimed to objective was to gather information about the combination of vitamin D deficiency and the presence of depression, and the influence on mortality in older adults. A search was carried out in the electronic databases BVS, Embase, Cochrane and PubMed, no restrictions on type of study, language or time, with the descriptors “depression”, “vitamin D deficiency”, “older adults”, “mortality”, and their variations. The initial search identified 302 articles. After excluding duplicates and papers that did not include all the descriptors of interest, two articles were included for this integrative review. It was identified that the studied population had low levels of 25(OH)D, and that this was associated with the occurrence of depressive symptoms. The joint analysis of depression and 25(OH)D deficiency, and the impact on mortality was performed in only one of the articles. In this study, depressed individuals with a higher risk of death had 25(OH)D deficiency. In conclusion, there was an association between depression and low levels of vitamin D, relating to higher mortality. These variables are modifiable, however, the literature presents little data in this context to allow decision making. Further research in the area may clarify the relationship between depression, vitamin D deficiency and mortality, and enable changes in the course of this outcome.